PERAN ORANG TUA DALAM MEMOTIVASI ANAK MASYARAKAT ADAT SUKU LAUT (MANTANG) PADA PROSES PEMBELAJARAN TINGKAT PENDIDIKAN SEKOLAH DASAR DI PULAU LIPAN DESA PENUBA KECAMATAN SELAYAR KABUPATEN LINGGA KEPULAUAN RIAU - Rinta Yuliana Mandasari; Bedriati Ibrahim; Bunari Bunari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Indigenous Peoples of the Sea Tribe (Mantang) is one of the tribes in Riau Islands Province which is categorized as an isolated society. These isolated or sea tribes are often identified as fools, backward, poor and always use magical powers (in their supernatural powers) in their lives. Indigenous Peoples of the Sea Tribe (Mantang) is a group of people who lack awareness and motivation about the importance of education for their lives are more advanced. The research aims to find out (1) to find out the history of the entry of primary school education to the children of Indigenous Peoples of the Sea tribe (Mantang) on Lipan Island Penuba Village (2) to find out how the role of parents in motivating Indigenous Peoples of the Sea Tribe (Mantang) children in Lipan Island Penuba Village to attend school (3) to find out the inhibiting factors for Indigenous Peoples of the Sea Tribe (Mantang) in providing educational support for their children. The method used in this research is descriptive qualitative. The results of this reaserch indicate that (1) the history of the inclusion of education in Lipan Island begins with the construction of a formal school that is SDN 006 Selayar (2) Indigenous Peoples of the Sea Tribe (Mantang) has been running the role of parents as a motivator and facilitator well in terms of paying attention to the education of his son (3) factors that become obstacles of children in carrying out the educational process that is the family's economic factors, the influence of environmental factors such as distance and time to school and low public mindset about education.Key Words: The Role of Parents, Education Motivation